Beethoven Oeuvres choisies edited by Marmontel, vol. 1 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Marmontel, Antoine François, 1816-1898 (editor):::Contributor:::::::::::: (France; Paris; Heugel et Cie., 2024)
First volume of the "Oeuvres choisies" of Beethoven edited by Antoine François Marmontel for the series "École classique du piano" published by Heugel & Cie. in Paris.